Prvky cizích pravopisů v pravopisu severocentrální romštiny - proměny v teorii a ediční praxi od počátku systematického pravopisu do přelomu osmdesátých a devadesátých let 20. století - Červenka, Jan (Romano džaniben, 2017)
The article traces the evolution of one of the orthographic principles for North–Central Romani in Czechia: marking of code-switching in Romani with the use of the orthographic system of the source language (Czech). The length of the period under estimation is determined by the publication of two texts prepared in the time of so-called perestroica but published only after 1989. The author comes to following periodization: the researched principle was first published not earlier than 1991 but it has been present in Romani as written in Czechoslovakia since the introduction of the orthographic system in the early 1970s. In the times of Svaz Cikánů–Romů (Union of Gypsies-Roms, 1969-1973), there was an explosive development of Romani journalism which brought a lot of code-switching into the texts. In the times of forced decline of Romani ethno-emancipation movement (1974-1989), social themes completely disappear from the texts published in Romani but that is also why Romani language published in that time becomes purist, although there is no support for Romani nationalism. Code-switching comes back into the texts with the revival of social themes only in the very last period of the communist regime and in the texts published after the fall of communism.